Numerical Analysis of a PVD-improved Embankment on soft clay - Class A and class C prediction of the Ballina test embankments - Sundström, Salomon (My University, 2023)
The construction of embankments on soft soil is challenging to engineers due to difficulties associated with their short and long-term stability. This thesis aims to utilize numerical modelling to analyse the behaviour of embankments on soft clay, with special focus on the Ballina test embankments. Two distinct predictions are made: one considering the presence of prefabricated vertical drains (PVDs) installed in the soil and another completely without PVDs. The constitutive model used is the Creep- SCLAY1S model in PLAXIS 2D. The obtained results are compared with on-site measurements to evaluate the effectiveness and reliability of the modelling approach. The thesis involves analysing available soil data and creating a representative soil profile, deriving input parameters for the constitutive model. Furthermore, a simple homogenisation technique is implemented to model the global effect of the PVDs, through changing the vertical hydraulic conductivity in the soil. A comprehensive sensitivity analysis is conducted to identify factors with a significant influence on the simulation results. The results for the PVD-improved embankment demonstrate satisfactory predictions with vertical and horizontal deformations aligning reasonably well when compared with measurement data over a 3-year period. Moreover, the implemented averaging technique effectively captures the enhanced consolidation settlements introduced by the PVDs over the time period. Comparisons with the unimproved embankment indicate little actual improvements in stability for the improved case in the first 3 years. However, spanning over a 40-year period, the vertical settlements approach the same order of magnitude for the two cases, and the horizontal displacements are significantly less for the improved embankment. Indicating a time-dependent nature of stability improvement using PVDs. Ultimately, the parameter derivation process and high-quality laboratory data are vital for accurate simulations. As revealed by the sensitivity analysis, there is significant variations in the results depending on which laboratory test is used to derive the preconsolidation pressure. The discrepancy can likely be attributed to the unusually high strain-rates used for the CRS laboratory tests, in combination with the unusually low strain rates adopted for the IL-tests – emphasizing the experience and skill required of the engineer in order to arrive at accurate predictions.
Keywords: Numerical modelling; creep; soft clay; test embankment; Creep- SCLAY1S; Vertical Drains; Prefabricated Vertical Drains; PVD